Agronomical and economic evaluation of various cultivation systems on meadow soil - Ferencsik, Sándor (Acta Agraria Debreceniensis, 2013)
The requirements and objectives of cultivation are in constant change. There are different cultivation aims if the objective is soil protection, the prevention of its moisture content or on areas with different precipitation supply or production site endowments. Based on the experimental database of the Institute for Land Utilisation, Regional Development and Technology of the University of Debrecen, Centre for Agricultural and Applied Economic Sciences and the KITE Plc., the various cultivation systems in Hajdú-Bihar country were examined with maize as indicator plant. The sample area can be found in the outskirts of Biharnagybajom on meadow soil. On the examined plot, spring strip basic cultivation, loosening and autumn ploughing were applied on 15-15-15 ha, respectively. At the time of taking undisturbed soil samples, soil conductivity measurements were also performed with a Penetronik penetrometer. Undisturbed soil samples were taken from each treatment before sowing (on 5th April 2012). The yield obtained in the strip cultivation treatment increased that of the ploughing and the loosening technology. The economic indexes are the most favourable in the strip cultivation.